MARRIAGE READINESS EDUCATION AMONG UNIVERSITY STUDENTS: ANALYSIS OF SELF-PREPARATION FOR MARRIAGE AND FAMILY LIFE - Hamzah, Rifqy Muhammad (EDUCATIONE, 2025)
Early marriage, declining marriage rates, and lack of readiness for marital life remain pressing social issues in Indonesia. These challenges are influenced by legal changes, socio-economic pressures, and limited access to marriage education. This study aims to analyze the level of self-preparation for marriage and family life among undergraduate students in the Primary School Teacher Education (PGSD) Program at UPI Tasikmalaya Campus. Employing a descriptive quantitative survey design, data were collected from 221 students across three cohorts using the Developmental Task Inventory (ITP). The results, processed with the ATP application, show that students’ readiness for marriage and family life remains at the individuality development stage, with mean scores between 6.50 and 6.61—below the overall developmental average. The lowest indicator was found in the aspect of self-preparation for marriage, highlighting specific gaps in practical understanding and readiness. The findings suggest that students require targeted guidance and counseling services focusing on emotional, financial, and communication skills to enhance their marriage readiness. This study concludes that comprehensive premarital education and counseling interventions in higher education settings are essential for fostering mature, well-prepared individuals capable of building harmonious families. The results are beneficial for educators, counselors, and policymakers in designing effective marriage readiness programs. Future research is recommended to explore intervention models and the impact of marriage education on marital outcomes.